Potential Therapies for Cerebral Edema After Ischemic Stroke: A Mini Review - Yao, Yi; Zhang, Yonggang; Liao, Xiaoyang; Yang, Rong; Lei, Yi; Luo, Jianzhao (Frontiers in Aging Neuroscience, 2021)
Stroke is the leading cause of global mortality and disability. Cerebral edema and intracranial hypertension are common complications of cerebral infarction and the major causes of mortality. The formation of cerebral edema includes three stages (cytotoxic edema, ionic edema, and vasogenic edema), which involve multiple proteins and ion channels. A range of therapeutic agents that successfully target cerebral edema have been developed in animal studies, some of which have been assessed in clinical trials. Herein, we review the mechanisms of cerebral edema and the research progress of anti-edema therapies for use after ischemic stroke.